Immune Checkpoint Inhibitor-Induced Cerebral Pseudoprogression: Patterns and Categorization - Urban, Hans; Steidl, Eike; Hattingen, Elke; Filipski, Katharina; Meissner, Markus; Sebastian, Martin; Koch, Agnes; Strzelczyk, Adam; Forster, Marie-Thérèse; Baumgarten, Peter; Ronellenfitsch, Michael W.; Steinbach, Joachim P.; et al. (Frontiers in Immunology, 2022)
Background: The inclusion of immune checkpoint inhibitors (ICIs) in therapeutic algorithms has led to significant survival benefits in patients with various metastatic cancers. Concurrently, an increasing number of neurological immune related adverse events (IRAE) has been observed. In this retrospective analysis, we examine the ICI-induced incidence of cerebral pseudoprogression and propose a classification system. Methods: We screened our hospital information system to identify patients with any in-house ICI treatment for any tumor disease during the years 2007-2019. All patients with cerebral MR imaging (cMRI) of sufficient diagnostic quality were included. cMRIs were retrospectively analyzed according to immunotherapy response assessment for neuro-oncology (iRANO) criteria. Results: We identified 12 cases of cerebral pseudoprogression in 372 patients treated with ICIs. These patients were receiving ICI therapy for lung cancer (n=5), malignant melanoma (n=4), glioblastoma (n=1), hepatocellular carcinoma (n=1) or lymphoma (n=1) when cerebral pseudoprogression was detected. Median time from the start of ICI treatment to pseudoprogression was 5 months. All but one patient developed neurological symptoms. Three different patterns of cerebral pseudoprogression could be distinguished: new or increasing contrast-enhancing lesions, new or increasing T2 predominant lesions and cerebral vasculitis type pattern. Conclusion: Cerebral pseudoprogression followed three distinct patterns and was detectable in 3.2 % of patients during ICI treatment. The fact that all but one of the affected patients developed neurological symptoms mandates vigilance in the diagnosis and treatment of ICI-induced cerebral lesions.